The Place of Web&Mobile Applications in Typography Education and Their Effect on the Learning Process - Şen, Ezgi (Fırat University, 2024)
Typography has a multidimensional structure that enables creative arrangements as well as information or message transmission. In this context, it is an important part of visual communication design as well as education. Typography education is an interactive course that includes theory and practice. Students develop typography-design practice together as well as the terms related to the field. Today, there are typography (education) applications on mobile and web in order to increase learning motivation in the course, to place the special concepts and rules of typography in the minds of the students and to reinforce the subject. Most of the applications are of foreign origin and most of them have been developed on specific topics. It is clear that in the application designs where the concept of gamification is used effectively, it is aimed to give information not directly but by gamification. Digital natives, also known as Generation Z, who have opened their eyes to today's world where technology rapidly affects every field, have different needs in the field of education unlike digital immigrants. Within the scope of this study, the place of gamification-based web and mobile applications in typography education was investigated with a special focus on digital natives. The typography (web/mobile) applications selected as a sample in the article were examined under the titles of content, interface design and gamification, and it was aimed to reveal their foreseeable contributions to the typography education process. The study concluded that typography (web/mobile) applications have the potential to take an active role in the learning process and can be defined as interactive educational materials.

Tipografi, bilgi ya da mesaj iletiminin yanı sıra yaratıcı düzenlemeleri de mümkün kılan çok boyutlu bir yapıya sahiptir. Bu bağlamda görsel iletişim tasarımının olduğu kadar eğitiminin de önemli bir parçasıdır. Tipografi eğitimi, içerisinde teorik ve uygulama barındıran etkileşimli bir derstir. Öğrenciler derste alana ilişkin terimlerin yanı sıra tipografi-tasarım pratiğini de birlikte geliştirmektedir. Derste öğrenme motivasyonunun artması, tipografiye ait özel kavram ve kuralların öğrencilerin zihninde yer etmesi, konunun pekişmesi için bugün mobil ve web üzerinde tipografi (eğitim) uygulamaları mevcuttur. Uygulamaların büyük bir kısmı yabancı kaynaklı olup, çoğunluğu belirli konu başlıklarında geliştirilmiştir. Oyunlaştırma kavramının da etkin olarak kullanıldığı uygulama tasarımlarında bilginin doğrudan değil de oyunlaştırılarak verilmesinin hedeflendiği açıktır. Teknolojinin hızla her alana etki ettiği günümüz dünyasına gözlerine açan dijital yerliler ya da bir diğer adıyla Z kuşağı, dijital göçmenlerden farklı olarak eğitim alanında farklı gereksinimlere sahiptir. Bu çalışma kapsamında oyunlaştırma temelli web ve mobil uygulamaların tipografi eğitimindeki yeri dijital yerliler özelinde ele alınarak araştırılmıştır. Makalede örneklem olarak seçilen tipografi (web/mobil) uygulamaları içerik, arayüz tasarımı ve oyunlaştırma başlıklarında incelenmiş, tipografi eğitim sürecine ön görülebilecek katkılarının ortaya konması amaçlanmıştır. Çalışmada tipografi (web/mobil) uygulamalarının öğrenme sürecinde aktif rol alacak potansiyele sahip olduğu, etkileşimli eğitim materyali olarak tanımlanabileceği sonucuna ulaşılmıştır.
TİPOGRAFİ EĞİTİMİNDE WEB & MOBİL UYGULAMALARIN YERİ VE ÖĞRENME SÜRECİNE OLAN ETKİSİ
Keywords: Interactive Narrative; Etkileşimli Anlatım